(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Abstract: this article explores the criteria that distinguish notional and functional words in the English language. Notional words, such as nouns, verbs, adjectives, and adverbs, carry semantic meaning and contribute to the content of a sentence. Functional words, on the other hand, such as prepositions, conjunctions, and articles, serve a grammatical purpose and provide structure to the language. The article delves into the defining characteristics of these two word classes and their roles in English grammar and communication.